The Effectiveness of Tripod Position And Pursed Lips Breathing to Enhance Oxygen Saturation in Patients With COPD - Hilma Wahidati Wahidati; Sri Utami Dwiningsih; Putrono Putrono (Poltekkes Kemenkes Semarang, 2019)
Background: COPD is a pulmonary disease characterized by air obstruction in respiratory tract from bronchi to the bronchioles, which continuously occur progressively, and irreversible, and related with the inflammatory response due to toxic gases (cigarette smoke, factory pollution and vehicle pollution) so it can cause a desaturation oxygen (SpO2). This impact will caused in concentration decreased, functional activity reduction, hypoxemia, hypoxia until cyanosis. To prevent this impact, there are two non-pharmacological methods that can be applied, a tripod position and pursed lips breathing exercise. Purpose: To determine the effectiveness of tripod position and pursed lips breathing to enhance oxygen saturation in patients with COPD.Methods: The research used queasy experimental with pre-posttest design. This research used total sampling that have 34 samples COPD patient which is include in inclusion criteria in working area of Puskesmas Padangsari Semarang. The samples are divided into 2 treatment groups (tripod position groups and pursed lips breathing groups) that gives 15 minutes therapy 3 times within 3 continuous days. This research will begins from February until March 2019. Statistical test to determine the affectivity of each groups using non-parametric test (Mann-Whitney test). Results: the result of this research shows differences effectiveness between tripod position and pursed lips breathing with p value 0.00 with mean deviation before and after therapy of tripod position 0.29 and pursed lips breathing 1.23.Conclusion: in this research shows that pursed lips breathing is most effective to enhance oxygen saturation in COPD patient compare with tripod position.